P5.009 Predictors of psychological and functional outcome following traffic injuries: a scoping review. (14th March 2021) - Alharbi, Rayan; Miller, Charne; Lewis, Virginia
Abstract : Background: Each year tens of millions of individuals are injured or disabled as a result of Road Traffic Crashes (RTCs). In addition to immediate death, there is an increased risk of subsequent death, ongoing physical disability, psychological issues, and reduced overall health related quality of life following RTCs. This study aims to identify the factors reported in the literature that are associated with adult trauma patients' morbidity following an RTC. Methods: A scoping literature review was conducted. Peer- reviewed articles were retrieved from MEDLINE/PubMed, EMBASE, and CINAHL. Results: This literature review identified six categories of variables being used in studies that explored predictors and factors associated with physical and psychological morbidity following RTCs. Five of the categories represented independent variables; (i.) injury characteristics and hospital predictive factors; (ii.) demographic factors; (iii.) family and social support; (iv.); compensation system process and fault in the RTC (v.); and pre-injury health status (vi.). The sixth category was used to represent the range of (vi.) psychological and functional outcomes. Conclusion: These findings highlight the multiple and diverse contributors that influence person outcomes following an RTC. These factors are intrinsic and extrinsic and commence from the time of injury as well as highlighting the importance for ongoing support after acute care discharge to enable a quick return to optimal wellbeing. Learning Outcomes: Research examining RTC outcomes must integrate information about the crash response and health care system whilst simultaneously measuring other factors to appropriately quantify the relative contribution of each variable to psychological and functional outcomes.